2021
DOI: 10.1109/access.2021.3100102
|View full text |Cite
|
Sign up to set email alerts
|

Calibration of Visibility Samples for Real-Time Passive Millimeter Wave Imaging

Abstract: A Ka-band 1024-channel passive millimeter wave (PMMW) imager with 1 GHz bandwidth called BHU-1024 has been developed by Beihang University for security screening. BHU-1024 uses linear phased array to obtain resolution in the horizontal direction and uses aperture synthesis to obtain resolution in the vertical direction. The non-ideal characteristics of the hardware cause the decrease of system sensitivity and always blur the reconstructed image, hampering applications where high resolution and accurate recogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…It consists of a low noise amplifier (LNA), an IRM, and a multiply-by-four LO chain which includes a drive amplifier, an analog phase shifter, a quadrupler and an absorption band-pass filter (ABF). Our previous work on real-time security imager (BHU-1024) has demonstrated that 4 GHz bandwidth is sufficient for measurement sensitivity [6]. In order to obtain relatively high gain with 0.15 μm GaAs pHEMT process, an operation frequency band of 52-56 GHz is selected for the receiver front-end.…”
Section: Integrated Receiver Front-end Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of a low noise amplifier (LNA), an IRM, and a multiply-by-four LO chain which includes a drive amplifier, an analog phase shifter, a quadrupler and an absorption band-pass filter (ABF). Our previous work on real-time security imager (BHU-1024) has demonstrated that 4 GHz bandwidth is sufficient for measurement sensitivity [6]. In order to obtain relatively high gain with 0.15 μm GaAs pHEMT process, an operation frequency band of 52-56 GHz is selected for the receiver front-end.…”
Section: Integrated Receiver Front-end Overviewmentioning
confidence: 99%
“…In addition, the front-end for radiometer application should have flat gain and low noise figure (NF) in wide operation band, because these parameters directly determine the radiometric sensitivity. For our security imager that uses a joint technology of phased array and synthetic aperture [6], the main requirements for the receiver front-end are: 1) gain flatness better than ±1 dB and NF less than 8 dB within 4 GHz operation band, and 2) a continuously adjustable phase-control range of 360°.…”
Section: Introductionmentioning
confidence: 99%
“…[4] Moreover, in order to improve imaging sensitivity, spatial resolution, and imaging rates, these systems are being developed toward achieving high integration and large-scale arrays. Beihang University proposed a PMMW imaging system (BHU-1024) for fast and non-cooperative security application scenarios, in which a phased array and a synthetic aperture work synergistically [5,6]. The phased array forms a fan beam and obtains the resolution in the horizontal direction via electric scanning.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in our previous work, a Ka-band passive imaging system was researched and reported [7]; the imaging system achieves better spatial resolution by using 1024 receiving channels, then a large number of correlators is needed for the imaging system. Therefore, compact size is also required for the analog correlator to reduce the size of the passive imaging system.…”
Section: Introductionmentioning
confidence: 99%